The Impact of Grid-Forming vs. Grid-Following Converters on Frequency Regulation: Comparing Centralised or Distributed Photovoltaic Generation - Giuseppe Marco Tina; Giovanni Maione; Domenico Stefanelli (Energies)
Energy transition strategies point to energy systems that rely mostly on renewable sources, with photovoltaics being the most commonly used and emphasised. The transition from the past to the future of electrical system is characterised by the contrast between centralised and distributed generation, as well as the differences between synchronous machines and static converters and thus by their way to deliver services required for proper system operation, frequency regulation and transient stability. This paper compares the two converter control strategies, grid following and grid forming, for providing frequency regulation service while considering bulk photovoltaic generation at the HV level and MV-connected distributed by PV generation. The analyses reveal the equivalence between large plants and distributed resources for frequency regulation purposes, highlighting the relevance of grid-forming converter and their ability to supply inertia to the system. These results are obtained for the IEEE 14-bus system implemented in Dig Silent PowerFactory.